2018
DOI: 10.1080/02699206.2018.1498541
|View full text |Cite
|
Sign up to set email alerts
|

Why is measuring communication difficult? A critical review of current speech pathology concepts and measures

Abstract: Human society is organised through communicative interactions between co-present people. Speech pathology (SP) assessment and intervention strategies aim to access these sites of communication in order to facilitate participation in life situations for people with communication disorders. Surprisingly, however, there is no explicit theory of communication underpinning SP practice and research. As a result, the conceptual and practical basis for rigorous, empirical measurement of communication remains limited, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 62 publications
0
45
1
Order By: Relevance
“…Firstly, any attempt to capture someone's communicative ability in a single number should be considered uninformative (Barnes & Bloch, 2018). The model delineates three major components, which in turn can be broken up into dif- speaking on the phone, sending an email or text message, or speaking face-to-face, it has been suggested that to evaluate the principles that govern situated language use, one can start by studying the most basic form: face-to-face communication (Barnes & Bloch, 2018;Clark, 1996;McDermott & Tylbor, 1983;Pickering & Garrod, 2004;Bavelas & Chovil, 2000), as it is the most commonly used and pervasive form of communication, it is universal to all human societies, it is the basis for typical language acquisition in children and it does not require education or special skills (Bavelas & Chovil, 2000;Clark, 1996). Indeed, Davidson et al (2008) showed that face-to-face conversation is the most frequently occurring communicative activity in daily life for PWA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, any attempt to capture someone's communicative ability in a single number should be considered uninformative (Barnes & Bloch, 2018). The model delineates three major components, which in turn can be broken up into dif- speaking on the phone, sending an email or text message, or speaking face-to-face, it has been suggested that to evaluate the principles that govern situated language use, one can start by studying the most basic form: face-to-face communication (Barnes & Bloch, 2018;Clark, 1996;McDermott & Tylbor, 1983;Pickering & Garrod, 2004;Bavelas & Chovil, 2000), as it is the most commonly used and pervasive form of communication, it is universal to all human societies, it is the basis for typical language acquisition in children and it does not require education or special skills (Bavelas & Chovil, 2000;Clark, 1996). Indeed, Davidson et al (2008) showed that face-to-face conversation is the most frequently occurring communicative activity in daily life for PWA.…”
Section: Resultsmentioning
confidence: 99%
“…This in turn is separated from their level of participation in everyday life, and the ICF also defines personal and external factors that might be of influence across these different levels of functioning. Barnes & Bloch (2018) argue that the ICF is not able to capture everyday communication as it gives a limited view of communication as a fundamentally individual competence, that can be standardized separately from different contextual variations. Glueckauf et al (2003) criticised the ASHA-FACS for measuring the degree of independence in communication (i.e.…”
Section: Standardized Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tools from conversational analysis offer rich promise in furthering our understanding of “co-present interaction” [39]. However, the potential power of these approaches is in tension with the time demands they imply.…”
Section: Innovations In Input/access Methodsmentioning
confidence: 99%